Injuries and persistent pain in elite adolescent archery athletes: A cross-sectional epidemiological study - Vasilis, N.; Kyriakides, A.; Vasilopoulos, G.; Chatzitimotheou, M.; Gonidakis, G.; Kotsakis, A.; Paraskevopoulos, E.; Kapreli, E. (Sports, 2024)
This cross-sectional epidemiological study aimed to evaluate the prevalence of injuries among young archers engaged in high-intensity training during the European Youth Championship. A total of 200 participants (104 males/96 females) from 34 countries were included, with a mean age of 16.9 years and average competitive experience of 6.5 years. Structured questionnaires, administered by four physiotherapist interviewers, gathered comprehensive data. Results revealed that 43.5% of participants experienced shoulder pain during training, highlighting the vulnerability of upper limbs in archers. Additionally, 30% required medications to facilitate training, underscoring the impact of injuries on continued participation. Physiotherapy was utilized by 52.3% of participants, emphasizing the need for therapeutic intervention. Furthermore, 31.8% had to cease training due to injuries, indicating a substantial hindrance to athletic progression. The mean pain duration was 3.9 months, with an average intensity of 5.94, and 8% exhibited symptoms of central sensitization. In conclusion, this study demonstrates a noteworthy prevalence of injuries, particularly in the upper limbs, among young archers undergoing intensive training. The findings underscore the importance of targeted injury prevention strategies and comprehensive rehabilitation approaches to ensure the well-being and sustained participation of young athletes in competitive archery.